Entering the Fifth Dimension: modular modernities, psychedelic sensibilities, and the architectures of lived experience. Issue 3 (24th March 2021) - Dickens, Luke; Edensor, Tim
Abstract : In this paper, we elaborate on the Fifth Dimension, an extraordinary, largely overlooked architectural example of 1960s psychedelia that was installed in a small Scottish resort town. Made up of 17 domed chambers, each designed to stimulate psychedelic sensory experiences for its intrepid visitors, the Fifth Dimension was the creation of London‐based environmental artist Keith Albarn using his experimental "Ekistikit" modular building system. We argue that the qualities and impacts of this highly inventive, utopian "fun palace" interrogate stereotypical depictions of countercultural, psychedelic creativities. We discuss how they also intersect with current geographical scholarship concerned with sensation, play, and the built environment. Two key elements of the Fifth Dimension are examined. First, building on critical geographies of architecture, we focus on Albarn's innovative system to exemplify how pioneers of environmental design used advanced modular technologies to radically re‐configure the possibilities of dwelling and working in flexible building structures. Second, drawing on aesthetic theories of the sensory, we demonstrate how the structure was designed to stimulate transformative psychedelic sensibilities as a novel form of disruptive politics to induce critical dispositions towards the built environment. Our argument is underpinned by the call for a recuperation of sensational and affective experience in the design and inhabitation of built environments. We contend that this bears particular significance for an emergent geography of play and enchantment. Abstract : In this paper, we elaborate on the Fifth Dimension, an extraordinary, largely overlooked architectural example of 1960s psychedelia that was installed in a small Scottish resort town. We argue that this highly inventive, utopian "fun palace" used advanced modular technologies to radically re‐configure the possibilities of dwelling, and deployed psychedelic sensibilities as a novel form of disruptive politics to induce critical dispositions towards the built environment. Our discussion engages current geographical scholarship concerned with sensation, play, and the built environment.